The Effectiveness of a Psychological Guidance Model in Enhancing Student Management Tolerance: A Quasi-Experimental Study at Universities in Bandung, Indonesia - Muhammad rezza Septian; Mamat Supriatna; Juntika Nurihsan; Nandang Budiman; Maya Masyita Suherman (G-Couns: Jurnal Bimbingan dan Konseling, 2026)
This study is grounded in the context of 21st-century education, which is marked by increasing diversity. Such conditions require students at both school and university levels to develop tolerance as a key multicultural competence. Previous research indicates that students’ tolerance levels remain moderate, with some showing low awareness in respecting differences, raising concerns about potential social conflict. To address this challenge, the present study introduces a psychological guidance approach as an intervention model to strengthen the cognitive, affective, and psychomotor dimensions of tolerance. A quasi-experimental pretest–posttest control-group design was applied to 66 students from a teacher education faculty in Bandung. ANCOVA results revealed a significant difference between the experimental and control groups (F = 37.944; p < .001), accompanied by a large effect size (r ≈ 0.814). These outcomes demonstrate that the psychological guidance model effectively enhances several indicators of tolerance, including persistence in managing differences, appreciation of diversity, and equal, non-discriminatory treatment of others. The study concludes that psychological guidance is a promising strategy for fostering tolerance in higher education settings. Future research should broaden the sample to include multiple institutions and employ qualitative methods to further explore the dynamics of tolerance development. Keywords: psychological guidance, model, student, tolerance